Kinerja Dinas Pendidikan dan Olahraga Dalam Peningkatan Literasi Digital Melalui Wajib Pojok Baca di Kabupaten Badung - Ni Made Sulastini (Cognoscere: Jurnal Komunikasi dan Media Pendidikan, 2023)
Reading is a mandatory activity carried out by students as an effort to support the smooth running of teaching and learning activities at school. However, in reality it can be said that the reading ability and interest of students, especially elementary school students, is still very low. One of the reasons for this is the lack of attention from schools or the government in providing facilities to support reading activities that can be carried out at school. One of the government's efforts to increase students' interest in reading is to require every school to create a reading corner where the books used are books that suit the needs of children at school according to their respective levels. So, from this reading corner, students are expected to be able to build enthusiasm and rebuild interest in reading in Badung Regency. This research was carried out at SDN 1 Sempidi using a descriptive qualitative method where data collection used interview techniques with sources who were believed to be able to provide information about the problem.